THE RELATIONSHIP BETWEEN FAMILY COHESION, ADAPTABILITY AND POSTPARTUM DEPRESSION AMONG PALESTINIAN WOMEN - Mayaleh, Boshra (An-Najah National University, 2024)
Abstract Background: The postpartum period involves significant changes for mothers and families, and the quality of family functioning can influence a mother's vulnerability to depression. Family environment, described using Olson’s family function theory, is a factor in postpartum depression, yet few studies have explored its application to mothers with this condition. Objective: To investigate the relationship between adaptation, family cohesion, and the risk of postpartum depression among Palestinian women and to identify the factors that predict family adaptation, family cohesion, and postpartum depression. Methodology: A cross-sectional descriptive study including 570 mothers of healthy babies aged between 2 weeks to 12 months, attending primary health care clinics in the West Bank from September 2023 to December 2023. Participants completed the Edinburgh Postpartum Depression Scale (EPDS) and the Family Adaptability and Cohesion Evaluation Scale III (FACES III). SPSS was used for analysis, employing linear regression and Sperman’s rank coefficient to assess associations between family cohesion, adaptability, and postpartum depressive symptoms. Results: Most mothers (58.9%) were aged between 18-27 and (64.9%) were unemployed. The EPDS results indicated that 88.1% of mothers were at risk of postpartum depression, with severity ranging from no symptoms (11.9%) to severe symptoms (32.2%). Family cohesion varied, with 32.28% connected, 25.79% separated, 32.81% disengaged, and 9.12% enmeshed. Regarding adaptability, 54.73% showed chaotic adaptability, 33.51% were flexible, 8.95% were structured, and 2.81% were rigid. Logistic regression showed that compared with connected families, enmeshed and separated were more likely to develop postpartum depression, while disengaged families were protective. Postpartum depression was not associated with any type of family adaptation, but all types were more protective against depression than flexible families. Conclusions: The study highlights a high prevalence of postpartum depression among Palestinian mothers, influenced by psychosocial stressors and family cohesion. A lower risk of depression correlates with higher scores of family cohesion. Family income, a history of depression, the number of births, previous miscarriages, employment status, intended pregnancy, mode of delivery, and baby age are significant predictors of postpartum depression. Family cohesion is predicted by maternal age, education, geographical area, and income, while adaptation is influenced by maternal education and geography. The high prevalence of postpartum depression indicates the mental health risks experienced by Palestinian women, and this requires prior intervention from the Ministry of Health and Women's Affairs. Keywords: Family cohesion, adaptability, Postpartum depressive symptoms, Palestine, FCAES III, EPDS.
العلاقة بين التماسك الأسري و القدرة على التكيف و اكتئاب ما بعد الولادة بين النساء الفلسطينيات